Fenomena Tradisi Nyekar pada Hari Jum’at Pahing di Makam Kanjeng Sepuh Sidayu Gresik - Ihsan, Moh Najib; Figo Setiyawan, Muhammad; Sholihah, Mar'atus; lailatul Maf'ulah , Nuril (Javano Islamicus, 2024)
Islam developed in Java in harmony with the culture of the surrounding community. Some Javanese cultures are still preserved and dialogued with Islam. One of them is the Nyekar cultural tradition at the tomb of Mbah Kanjeng Sepuh in Sidayu Gresik. This article discusses this from the perspective of the Prophet's hadith. This article uses a qualitative method, presented descriptively with two main sources, namely literature review and field study. From the results of the study, it was found that the Nyekar tradition at the tomb of Mbah Kanjeng Sepuh is an activity that is usually carried out by a group of people on the Javanese Pahing market day and is most crowded on Friday Pahing. This activity is carried out based on the Prophet's hadith regarding the permissibility of visiting graves.